Blue Smoke - Roberts, Nora (New York : G.P. Putnams Sons, 2021)
Pursuing a career as an arson investigator after a fire destroys her familys pizzeria, Reena Hale embarks on a relationship with Bo Goodnight and finds herself targeted by an arsonist who taunts her with threatening phone calls.
Keywords: Arson investigation -- Fiction; Women -- Maryland; Fiction; Pyromania -- Fiction; Psychopaths -- Fiction; Baltimore (Md.) -- Fiction; Psychological fiction; Thrillers (Fiction); Romantic suspense fiction